The attachment of a vehicle with retention of title in favour of the creditor - Magalhães SILVA, Maria José (Revista Jurídica Portucalense, 2025)
In the context of the motor trade, the nature and function of retention of title has given rise to lively debate and dissenting decisions in case law and doctrine. The most debated points relate, on the one hand, to the possibility of the retention of title being agreed in favour of a third party, usually the funding entity, either ab initio or as a result of the transfer of the legal position of the seller, and, on the other hand, to the nomination to seizure of the vehicle object of the legal transaction in which the retention of title has been stipulated. In this paper, we will approach the subject from two premises: Reservation of ownership stipulated in a vehicle sale contract in favour of the seller, who is simultaneously the funding entity, though also referring to the possibility of transferring the position of the seller to the funding entity; and The option to enforce the contract by attachment of the vehicle itself or by attachment of the debtor's acquisition expectation. The text develops to the issue of registering the attachment (whether of the vehicle or of the acquisition expectation), addressing different possibilities for the decision of the Registrar and for the nature of the registration to be made, with reference also to IRN doctrine on the matter.